Cough Radiculopathy: Postinfectious Cough-Related Acute Lumbar Radiculopathy - Samer Alkhuja (Case Reports in Medicine)
Cough is a protective reflex of airways and lungs. Cough may result in several complications. Postinfectious cough is a cough that begins during an acute respiratory tract infection, usually is self-limited, and is due to airway hyperresponsiveness as a result of airway inflammation. Cough radiculopathy has been once reported by Torrington and Adornato in the form of acute cervical radiculopathy. This is a case of acute lumbar radiculopathy as a result of postinfectious cough. Literature review did not show a similar case.